Acute appendicitis caused by foreign body ingestion - Kim, Joo Heung (Ann Surg Treat Res, 2015)
Foreign bodies usually do not cause complications and pass through the gastrointestinal tract spontaneously. Usually endoscopic intervention is recommended within 24 hours. Cases of acute appendicitis caused by foreign bodies are very rare. In our case, we experienced successful endoscopic and surgical treatment of a patient with ingestion of razor blade and some unrecognizable foreign bodies. A 22-year-old soldier was admitted with a small quantity of hematemesis and epigastric pain. We performed emergent endoscopy and successfully removed several foreign bodies. After 17 days, we performed appendectomy to remove the remaining foreign body and to relieve the symptoms. There is no doubt that endoscopic intervention is definitely useful method to remove foreign bodies. If there is no spontaneous drainage of the foreign body from the appendix, an appendectomy must be considered to remove the foreign body and prevent surgical complications such as appendicitis, periappendiceal abscess, and perforation.